Implications of Accounting and Tax Treatment of Cryptocurrencies - Ivana Martinčević; Vesna Sesar; Krešimir Buntak (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
The digital revolution is changing everyday business and creating new technologies and tools that allow companies flexibility and simplicity in doing business and increase business performance. The digital age creates new concepts that also affect accounting processing, which presents new challenges in accounting practice. One of the most significant changes and innovations within accounting processing and the financial industry is the emergence of cryptocurrencies that create a completely new financial business concept. Cryptocurrency is the equivalent of electronic money and is completely digital. Although cryptocurrencies and transactions with cryptocurrencies are frequent appearances in today's modern business, accounting and tax treatment in the Republic of Croatia and other European Union countries but also beyond is not fully established and adjusted for doing business with cryptocurrencies, which requires strict regulation and adjustment operations with cryptocurrencies. As cryptocurrencies become more popular, so do taxes on cryptocurrencies that vary from country to country. Cryptocurrencies are associated with risks such as money laundering, terrorist financing, and tax evasion, which require the establishment of a regulatory body and the implementation and application of regulations in the function of the transparent business with cryptocurrencies. This paper aims to investigate the characteristics of cryptocurrencies and their financial, accounting, and tax treatment.
Keywords: Q33; H25; H26; M21; M41; 330; money; cryptocurrencies; blockchain technology; financial system; accounting; taxes